Caffeine ingestion and performance of a 1,500-metre swim - MacIntosh, B. R.; Wright, B. M. (Canadian Journal of Applied Physiology, 1995)
The purpose of this study was to evaluate the potential ergogenic benefit of caffeine in the performance of a 1,500-meter swim. Caffeine (6 mg.kg-1) or placebo was administered 2-1/2 hrs prior to the swim trial in a double-blind crossover design. Caffeine resulted in a significantly lower perceived exertion for 100-m warm-up swims. Subjects swam significantly (p < 0.05) faster with caffeine (20:58.8 +/- 0:36.4, mean +/- SEM) than without (21:21.8 +/- 0:38). Plasma potassium was significantly lower prior to the swim with caffeine, and blood glucose was higher after that swim. Caffeine provides an ergogenic benefit for a 1,500-meter swim, an event that is completed in less than 25 min. Lower plasma potassium concentration prior to exercise and higher blood glucose following the trial suggest that electrolyte balance and glucose availability may be important aspects of the ergogenic effects of caffeine.